DYSLIPIDEMIA WITH ALTERED OXIDANT-ANTIOXIDANT STATUS IN RHEUMATOID ARTHRITIS - KOWSALYA R; SREEKANTHA; VINOD CHANDRAN; REMYA (International Journal of Pharma and Bio Sciences, 2011)
Rheumatoid arthritis is a clinical condition accompanied by inflammation and oxidative stress. In this study, we compared levels of antioxidants vitamin-E and C along with lipid profile between rheumatoid arthritis patients and healthy controls. We also looked into presence of any correlation between dyslipidemia, the antioxidants vitamins and lipid peroxide product among rheumatoid arthritis patients. We found a significant fall in vitamin E and C along with raised MDA in patients compared to controls. A highly significant positive correlation was found between MDA and LDL-cholesterol (r = 0.781,P< 0.004),whereas vitamin E and C were negatively associated with MDA level (r = −0.70, P< 0.01 and r = −0.75,P< 0.001 respectively).Thus the assessment of the lipid profile,along with other cardiovascular risk factors should be actively determined and appropriate treatment along with sufficient antioxidants supplementation should form part of the standard treatment protocol in rheumatoid arthritis patients.